2017
DOI: 10.1073/pnas.1614268114
|View full text |Cite
|
Sign up to set email alerts
|

ACSS2-mediated acetyl-CoA synthesis from acetate is necessary for human cytomegalovirus infection

Abstract: Recent studies have shown that human cytomegalovirus (HCMV) can induce a robust increase in lipid synthesis which is critical for the success of infection. In mammalian cells the central precursor for lipid biosynthesis, cytosolic acetyl CoA (Ac-CoA), is produced by ATPcitrate lyase (ACLY) from mitochondria-derived citrate or by acetylCoA synthetase short-chain family member 2 (ACSS2) from acetate. It has been reported that ACLY is the primary enzyme involved in making cytosolic Ac-CoA in cells with abundant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 61 publications
1
71
0
Order By: Relevance
“…We then employed LC-HRMS to enable spectral resolution of [ 18 O 1 ]-acetate from other isotopically labeled species. Analysis of the incorporation of 18 O into tryptophan-related metabolites that are produced through oxygenation and stable labeling after 48 hrs demonstrated that 45% of the total O 2 is 18 O labeled in this setup (Fig. 2c).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…We then employed LC-HRMS to enable spectral resolution of [ 18 O 1 ]-acetate from other isotopically labeled species. Analysis of the incorporation of 18 O into tryptophan-related metabolites that are produced through oxygenation and stable labeling after 48 hrs demonstrated that 45% of the total O 2 is 18 O labeled in this setup (Fig. 2c).…”
Section: Resultsmentioning
confidence: 88%
“…2a top), and the reaction would involve incorporation of the oxygen into H 2 O 2 via production of superoxides and then into acetate. H 2 O 2 thus obtains oxygen from molecular O 2 and therefore, culturing cells in the presence of 18 O 2 and monitoring incorporation of 18 O into peer-reviewed) is the author/funder. All rights reserved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous system-level examination of metabolites and their fluxes found that HCMV infection resulted in remodeling of carbon metabolism (Chambers et al 2010;Munger et al 2006;Purdy et al 2015;Vastag et al 2011;Hwang et al 2014). The flow of carbons from glucose to fatty acid metabolism is increased, possibly involving the non-enzymatic conversation of a pyruvate to acetate to generate the substrates required for fatty acid synthesis and elongation (Vysochan et al 2017). Likewise, carbons from glutamine are redirected for anaplerotic usage to replenish the TCA cycle (Munger et al 2008;Chambers et al 2010).…”
Section: Manipulation Of Host Metabolismmentioning
confidence: 99%